Application of micro-calorimeter for metabolic monitoring - Tan, Yi Jun (2015)
This project aims to develop an optimized experimental set-up of a microcalorimeter for metabolic monitoring applications. In order for an optimization to take place, a PolyDiMethylSiloxane (PDMS) cover was designed and fabricated to reduce the external noise which will in turn improve the accuracy of the readings collected by the microcalorimeter. The PDMS cover will minimise external noise and confine the sample physically which will reduce errors due to evaporation. Several methods of bonding for the PDMS cover and the microcalorimeter were experimented and tested(Integration, 2013).